Google Meeting App: As Electronic Feedback in Learning to Improve Students’ Writing Skills - Amrizal Amrizal; Zohri Hamdani; Candraning Prihatini (Universitas Negeri Semarang, 2022)
Writing is one of the difficult skills in English that must be mastered for English language education students in Indonesia. One of the reasons is because of the different grammar rules between Indonesian and English, which needs to be overcome for students' writing to increase by using the Google Meeting APP in the learning process. This study aimed to find out the effect of the Google Meeting App as electronic feedback in learning to improve students’ writing skills. This study was quasi-experimental in design. This was conducted in UIN Raden Intan Lampung, the fourth semester, students’ English Language Education. This had a sample of 30 students as a cluster class in this study. To collect data in this study used a pretest and a post-test. The SPSS 16.0 App was used to analyze the data for this study. This study shows that using Google Meeting APP as electronic feedback in learning can improve students’ writing skills. This means that this Google Meeting App had a good effect in the learning process, as students' writing skills improved.